MULTICULTURAL SOCIETY HORIZONTAL DIMENSIONS - Firmansyah, Firmansyah (Journal of Applied Transintegration Paradigm, 2021)
Abstract: The structure of Indonesian society is characterized by two unique characteristics, namely (1) horizontally, it is marked by the fact that there are social units based on differences in ethnicity, religion, customs, and regional differences. Meanwhile, (2) vertically, the structure of Indonesian society is marked by sharp differences between the upper and lower layers. The plurality of Indonesian society is a strength in itself, with a pluralistic society instilling values ​​of tolerance, mutual respect for differences and diversity in Indonesian society. The concept of plural society as used by social scientists today is indeed an extension of Furnivall's concept. Pluralism in Indonesia has developed in society since the colonial period of the Dutch East Indies, divided into three parts, namely European, Indigenous and Asian descent.